Revised filed Report on survey of a sample of the Sheko cattle maintained at the former Tolley Military Training Center - Workneh, A. (2001)
Breed descriptor variables were measured and blood samples collected at the end of June 2001 from the surviving 70 animals of the Sheko breeding herd temporarily maintained in the Tolley military training camp. These cattle descended from the 370 foundation herd of the Beggie Cattle Ranch, which was established to improve the Sheko breed particularly for milk, but demolished by rioters during the political instability and change of government in 1991. Although the Sheko cattle are known to be the only surviving taurine type cattle in eastern Africa, some of these animals manifest uncharacteristic humps and dewlap, indicating a possible interbreeding with neighbouring Zebu, Sanga and Zenga populations. Physical body measurements were taken from a selected subset of 7 cows and 3 bulls recognised as true Sheko type animals. Body size is small to dwarf (height at withers of 104cm, body length of 101cm and heart girth of 136cm), comparable to those of West African Shorthorns. Mature males and females weighed 208 and 188 kg, respectively. The coat colour is predominantly red in plain, patchy or spotted pattern. The Sheko are known to be better milkers than other types of cattle within the tsetse infested zone; however, no record was available on lactation during this visit.